Penerapan Model Project Based Learning (PjBL) melalui Proyek Rastik Untuk Meningkatkan Literasi Sains Siswa Sekolah Dasar - Sugiyanti, Nanik; Wicaksono, Iwan; sudarti, sudarti; Wuryaningrum, Rusdhianti (PGSD Universitas Muria Kudus, 2025)
The purpose of this study was to improve the science literacy of fifth grade elementary school students by implementing the project based learning (PjBL) model through the rastik project. The method used in this study is a quasi-experimental study, namely conducting treatment activities with the project based learning model through the rastik project. The design of this study uses a pre-test post-test control group design. The subjects of the study were 25 fifth grade elementary school students from SDN Sombo Gucialit as the experimental class and SDN Jeruk 01 as the control class. Data collection techniques used test and non-test techniques. Data analysis was carried out using the t-test. Based on the results of the paired sample t-test in Table 3, it is known that the Sig. (2-tailed) score is 0.002 <0.05. Therefore, the null hypothesis (Ho) can be rejected, and the alternative hypothesis (Ha) is accepted. Therefore, it can be concluded that there is a significant difference in the average value between the pretest and posttest results. This can be interpreted that the application of the PjBL model through the Rastik project can improve students' scientific literacy skills.